A review of CO2 corrosion inhibition by imidazoline-based inhibitor - Jaal, R.A. (EDP Sciences, 2014)
Carbon dioxide (CO2) corrosion is one of the most significant forms of attack in the oil and gas production and transportation systems. Corrosion inhibitors have been widely used in an effort to reduce the detrimental effect of the corrosion process. Different types of corrosion inhibitors have been applied for this purpose. The most frequent is the imidazoline-based inhibitors (IM), owing to their good adsorption characteristics and film-forming capability. Albeit their extensive use, their inhibition mechanism is not fully understood. This paper highlights the inhibition mechanism of IM and also the factors that contribute to its inhibition mechanism. Â© 2014 Owned by the authors, published by EDP Sciences.